Fiduciary in Civil Law and Bankruptcy Law Perspective - Herry Polontoh; Frans Reum (Publikasi Indonesia, 2024)
The fiduciary gives the creditor the right to pledge his property to the debtor as security for the debt given. In practice, there are often disputes between creditors and debtors related to fiduciaries. This dispute can occur due to various factors, such as the default of the debtor or the bankruptcy of the debtor. The purpose of this study is to identify and analyse the regulation and practice of fiduciaries from the perspective of civil law and bankruptcy law. This study used normative research methods. Data collection techniques are carried out by literature study. The data that has been collected is then analysed in three stages, namely data reduction, data presentation and conclusions. The results showed that fiduciaries, in the perspective of civil law and bankruptcy law, are a type of guarantee provided by fiduciaries to other parties in terms of collateral transactions. Fiduciaries are generally included in the fiduciary guarantee, which is a guarantee received by the party applying for financing to guarantee payments to be made by the fiduciary to the party applying for financing. From a civil law perspective, legal liability is for a fiduciary who transfers or leases the object of a fiduciary guarantee to another party without the written consent of the fiduciary beneficiary. Whereas in the perspective of financial law, a fiduciary assigns or leases the object of fiduciary guarantees to another party without the written consent of the fiduciary recipient.